Pathologic responses in oligometastatic NSCLC patients treated with neoadjuvant immune checkpoint blockade with and without chemotherapy followed by surgery. (February 2022) - Boch, Tobias; Frost, Nikolaj; Sommer, Linna; Overbeck, Tobias R.; Michaeli, Christoph T.; Szuszies, Chrisoph J.; Rieckmann, Lisa-Marie; Beumer, Niklas; Imbusch, Charles D.; Winter, Hauke; Thomas, Michael; Roeper, Julia; et al.
Highlights: NSCLC patients with oligometastastic disease benefit from locally ablative and systemic therapy. Neoadjuvant immunotherapy results in high pCR and MPR rates. Neoadjuvant immunotherapy is a promising therapeutic concept for oligometastastic disease. Abstract: Objectives: Immune checkpoint inhibitors (ICI) have significantly improved outcome of patients with advanced NSCLC and recently also showed benefit in early-stage disease. Patients with oligometastatic disease (OMD) harbor limited metastases, resectable primary tumors and derive benefit from treatment with multimodal locally ablative and systemic therapy approaches. Nothing is known about feasibility and efficacy of neoadjuvant ICI in this setting. Material and methods: We here provide data from a multicenter retrospective study comprising 13 patients with NSCLC and OMD (≤3 distant metastases) from 5 university medical centers in Germany who have been treated with neoadjuvant ICI alone (n = 4) or in combination with chemotherapy (CT) (n = 9) prior to resection of the primary tumor. We analyzed complete (pCR) and major pathological remission (MPR) rates. Results: These data show that neoadjuvant immunotherapy applied mostly in combination with CT results in high rates of pCR and MPR (54 and 69%, respectively). Up to now, 85% of patients are free of progression with a median follow-up of 9 months (3–28 months). Single cell RNASeq analysis of tumor tissue from one patient treated with CT-ICI indicates a strong predominance of adaptive immune cell populations over a small minority of epithelial (tumor) cells. Conclusion: Neoadjuvant ICI with or without CT is a promising therapeutic concept in patients with OMD.